Evaluasi Penerimaan Aplikasi Pusat Pelayanan Pengaduan Masyarakat (P3M) yang Diimplementasikan di Kabupaten Sidoarjo Berdasarkan Model Unified Theory of Acceptance and Use of Technology (UTAUT) - Zul Afrianes Pratama; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sidoarjo Regency Government has an e-government service called P3M (Pusat Pelayanan Pengaduan Masyarakat) which is implemented to accommodate various public aspirations and complaints. Based on the Citizens Satisfaction Index (IKM) survey in the first semester of 2019, P3M application only worth as 64.7 (not good), besides that, the P3M itself stated that the media that was the favorite of the citizens to submit their complaints was not P3M application, but Facebook. This study aims to describe the acceptance of the citizens of Sidoarjo Regency to P3M applications based on the Unified Theory of Acceptances and Use of Technology (UTAUT) framework that employed performance expectancy, effort expectancy, social influence, trust of the internet, trust of the government, trust of the CSC, facilitating conditions, behavioral intention, and use behavior. Data collection is done by distributing an online questionnaire that contains a total of 25 questions to 100 samples selected based on purposive sampling criteria. The research data was processed using a descriptive statistical approach and results were found the acceptance of the citizens of Sidoarjo Regency toward P3M applications based on the UTAUT model was categorized as high (61.91%). However, there are four variables that have below-average values, i.e. trust of the internet, trust of the government, trust of the CSC, behavioral intention, and use behavior. As a recommendation, these variables need to be optimized for implementation improvement in the future.